Screening of hypoglycemic effect and antioxidant potential of trewia nudilfora leaf extracts - Rashed, Mymuna (BRAC University, 2015)
This project report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2015